Linguocultural stereotypes of birds-soothsayers in the works of Mykhailo Stelmakh - Серебрянська, Ірина Миколаївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
The article presents the results of a linguistic and cultural study devoted to the problem of verbalization of the concepts of birds, which in the Ukrainian worldview are given special opportunities to predict human destiny. The relevance of the study is related to the key role of birds and their stereotypes as important components of the national language picture of the world and the works of M. Stelmakh in particular. The aim of the article is to find out the peculiarities of verbalization of bird concepts, which are associated with negative perceptions in the Ukrainian ethnic group, to outline their traditional symbol meanings, and new associations due to the historical era, as well as to substantiate their estimated value. Proverbs and sayings as apt pearls of folk wisdom convince that birds have been an object of admiration for Ukrainians, a subject for comparison, formulation of their own conclusions about the world of nature and its impact on human life and activity. The crow, the owl, and the bat are not just concepts of birds, but concepts-symbols, concepts-soothsayers. The most relevant national and cultural stereotypes about them in the Ukrainian-language picture of the world do not lose their relevance and acquire a kind of manifestation in literary texts. They are based on primary religious beliefs, national experience, and folk traditions. In M. Stelmakh’s literary works the folk symbolism of these birds acquires a special relevance, which is best manifested in the syntagmatic ties of their key nominations. The general negative evaluation inherent in the outlined concepts is due to the relevant features of denotations, their external, behavioral characteristics, beliefs and observations established in the Ukrainian language picture of the world. In context, the negative features sometimes turn into positive ones, and lexical means of exposing the evil, become a means of humor, fascination with birds as realities of nature, to which Ukrainians have always shown respect and love. The ambivalence of the concepts of soothsayers is a national-cultural stereotype that embodies the evaluative norms and values of the ethnos at the level of relationships and interaction of two important concept spheres – nature and man. In literary texts, they become evaluative examples for comparing the objects of society and their properties.